2012
DOI: 10.1097/ijg.0b013e3181fc8020
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Results of Selective Laser Trabeculoplasty in Open-angle Glaucoma in Japanese Eyes

Abstract: The 360-degree SLT was shown to be more effective than180-degree SLT for intermediateterm reduction in IOP of Japanese patients with open-angle glaucoma as an adjunctive treatment protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
2
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 19 publications
4
45
2
3
Order By: Relevance
“…Most reported adverse effects for SLT such as discomfort, pain or photophobia are mild and resolve within few days without treatment [34, 35]. The transient IOP rise of ≥5 mmHg occurs in 0 to 28% of eyes studied, [13, 36, 37] and ≥10 mmHg in up to 5.5% of eyes [13, 23]. It usually resolves quickly with or without topical antiglaucomatous treatment, usually within 24 h. Other side effects reported in the literature are: peripheral anterior synechiae, hyphema, bilateral anterior uveitis and choroidal effusion [36, 38, 39].…”
Section: Discussionmentioning
confidence: 99%
“…Most reported adverse effects for SLT such as discomfort, pain or photophobia are mild and resolve within few days without treatment [34, 35]. The transient IOP rise of ≥5 mmHg occurs in 0 to 28% of eyes studied, [13, 36, 37] and ≥10 mmHg in up to 5.5% of eyes [13, 23]. It usually resolves quickly with or without topical antiglaucomatous treatment, usually within 24 h. Other side effects reported in the literature are: peripheral anterior synechiae, hyphema, bilateral anterior uveitis and choroidal effusion [36, 38, 39].…”
Section: Discussionmentioning
confidence: 99%
“…26 Baseline IOP also seems to affect the overall reduction in IOP and may serve as a predictor for response to 360-degree SLT. In a study by Shibata et al, 27 pretreatment IOPZ21 mm Hg resulted in a more dramatic decrease in IOP compared with a baseline IOP<21 mm Hg (33.5% ± 17.4% vs. 22.4% ± 17.9%; P<0.05, respectively) in Japanese patients treated with 360-degree SLT. Intermediate amounts of treatment have also been evaluated, and Pehkonen and Valimaki 28 reported that the effect of 270-degree SLT falls within the same range as 180-degree SLT, resulting in a 4.7 ± 3.1 mm Hg (20%) reduction from baseline 6 months after treatment.…”
Section: Laser Trabeculoplastymentioning
confidence: 86%
“…Le traitement de 360 • de l'angle iridocornéen donne les meilleurs résultats [10,11]. Par ailleurs, le taux de succès dépend de la définition de « succès », plus ou moins sévère selon les études.…”
Section: Discussionunclassified